The Effect of Methyl Farnesoate Hormone on Reproduction in Crustaceans - Bal, Mehmet; Harlioğlu, Ayşe Gül (Centenary University, 2021)
Artificial production of crustaceans has gained importance on a global scale with the increase in demand. For this reason, studies are carried out to increase reproductive efficiency with hormone applications in aquaculture studies of economically important crustaceans. Studies on egg production have intensified with hormone application in the rearing of crustaceans. For this purpose, hormones such as neuropeptides, opioids, vertebral steroids, and methyl farnesoate (MF) are used. Methyl farnesoate is a hormone that is chemically similar to insect juvenile hormone III but differs from this structure by the absence of an epoxide group. It has been determined that MF has important functions in protein synthesis, moulting, morphogenesis, metamorphosis, and reproduction in crustaceans. It has been determined in crustaceans that exogenous testosterone, progestogen, juvenile hormone III, and MF increase sperm quality and reproductive efficiency in male decapods. In this review article, studies on the effects of MF hormone applications on reproduction in different crustacean species are discussed. © 2021, Centenary University. All rights reserved.
Metil Farnesoat Hormonunun Kabuklu Su Ürünlerinde Üremeye Etkisi
Keywords: Crustaceans; Hormone; Methyl farnesoate; Reproduction